Transient ST Segment Elevation in Two Patients with COVID-19 and a Normal Transthoracic Echocardiogram - Asif, Talal (Eur J Case Rep Intern Med, 2020)
We continue to learn about cardiac involvement in patients with COVID-19. These patients can develop acute coronary syndrome and severe myocarditis with a reduced ejection fraction. We describe two critically ill COVID-19 patients who developed ST elevation that resolved on repeat ECG without any intervention. LEARNING POINT: ST elevation may occur in critically ill COVID-19 patients.